공동주택 주동형태별 세대위치에 따른 일사분석 및 난방부하 절감요소에 관한 연구 - 김수정; 박두용; 김강수; Kim, Soo-Jeong; Park, Doo-Yong; Kim, Kang-Soo (生態環境建築, 2013)
This study aims to evaluate the correlation between vertical solar radiation and the level of heating load according to the location and type of housing in multi-family apartments. This study shows that heating load is related with factors such as wall loss, window loss, ventilation loss and solar radiation gain. The heating load increases in the order of the middle floors, the highest floors and the lowest floors. The lowest and the highest floors are the most vulnerable floors, and it should be as emphasized as the middle floors. The heating load saving proposal contains 52 Alt. that shows heating load savings from min. 4% to max. 49%. The goal is to reduce the heating load of the highest and the lowest floors to the level of the middle floors. The result showed that there are 3 Alt. for the lowest floors and 16 Alt. for the highest floors as the heating load saving proposal. This study suggests integrated application to compose saving elements of heating load. so it could be utilized as a data for the construction of passive houses.